The Influence of Work Discipline and Work Environment on Employee Performance - Yusuf, Muhammad; Suwardana, Hendra; Shoimah, Nikmatus (INNOVATION RESEARCH JOURNAL, 2024)
This research is aimed at examining the impact of work discipline and work environment on employee performance. This research applies an associative method with a quantitative approach. The research sample was taken using the method sample random sampling with a total of 75 respondents. Data was obtained through distributing questionnaires whose validity and reliability were tested. The data analysis technique was carried out using multiple regression analysis using SPSS. The results of the analysis show that the data is valid and reliable based on validity and reliability tests. The classical assumption test also shows that the data is normal, without multicollinearity and without heteroscedasticity. The results of the hypothesis test show that individual work discipline does not have a significant positive influence on employee performance. On the other hand, the individual work environment has a significant positive influence on employee performance. Simultaneously, work discipline and work environment have a significant influence on employee performance. In addition, the coefficient of determination test shows that the independent variable influences the dependent variable